History Ideas from Heritage of Building Sites Negeri Malayu Padang Kingdom in Tebing Tinggi - Nanang Arianto; Datuk Imam Marzuki; Siti Rahma Harahap; Susanti Hasibuan; Elismayanti Rambe (Budapest International Research and Critics University, 2021)
Historical and archaeological heritage for religious purposes, especially in the area. The conservation of the cultural heritage of the Padang Malay Kingdom in Tebing Tinggi requires the role of various parties such as the city government, cultural observers, academics and community participation in a social movement that loves local architecture to foster a sense of pride in the local artifacts that still exist. Therefore, this study describes the meaning of the idea as well as the government's attention from the legacy of the Malay Kingdom of Padang, Tebing Tinggi City. By using research methodology Interpretation is an effort to achieve a correct understanding of facts, data and symptoms. Using the theory of cultural areas (Trancik, 1986), namely an integrated area is an area consisting of elements physically having an orderly structure, normally paying attention to actors, cultural context, and roots, and functionally having an integrated network. The integration components in the aspect of norms describe cultural values and behavior of taste, creativity, and initiative.